Acute Respiratory Infection Among Brick Kiln Worker in Banjarnegara, Indonesia and Its Related Factors - Setyo widodo; Siwi Pramatama Mars Wijayanti; Agatha Sih Piranti (Public Health Department, Faculty of Health Sciences, Jenderal Soedirman University, 2020)
Background Occupational risk factors are one of the primary causes of acute respiratory infection (ARI). The high incidence of ARI in Banjarnegara Regency due to the process of bricks manufacturing is needed for further investigation. Objectives: This study aims to analyze risk factors such as air quality, tenure, smoking habits, the use of masks, knowledge of ARI incidence. Methods: This is an analytic study with a cross-sectional design. 342 of brick workers in three villages in Banjarnegara Regency were involved in this study. Air quality examination on dust particles, temperature, humidity, smoke, and air germ numbers was carried out in 15 of the brick kiln. Data about the duration of work, smoking habits, knowledge of ARI, and the use of masks were obtained by a structured questionnaire. Results: This study highlighted that the duration of work was the most influential variable in ARI incidence. Smoking habits and the use of personal protective equipment (mask) while working also correlated with ARI. Conclusion: This study suggested the regular use of a face mask while working to prevent the workers from dangerous pollutants. Periodic medical check-ups for workers and health education are also important prevention to be carried out to reduce ARI incidence.